Qumran Cave 1 revisited : texts from Cave 1 sixty years after their discovery : proceedings of the Sixth Meeting of the IOQS in Ljubljana - Falk, Daniel K. (Studies on the texts of the desert of Judah, 2010)
This volume contains a selection of the papers presented at the sixth meeting of the International Organization for Qumran Studies, held in 2007 in Ljubljana, Slovenia, on the topic a oeQumran Cave 1 Revisited: Reconsidering the Cave 1 Texts Sixty Years after Their Discovery.a While the opening paper assesses theories about the character of Qumran Cave 1 in relation to the other Qumran caves, all other papers discuss texts from Cave 1, in particular six of the seven large scrolls found there in 1947: the two Isaiah scrolls, the Rule of the Community, the War Scroll, the Thanksgivings Scroll, a.